A passive thermal control method by radiative shield with multi-parameter adjustment capacity. (5th February 2016) - Sun, C.; Wang, Z.Y.; Chen, X.; Xia, X.L.
Highlights: The radiative shield thermal control method is proposed and analyzed. There are 7 adjustable parameters in which radiative properties dominate. Thermal control effects are prior to thermal insulation method in this situation. Abstract: To ensure the stability and reliability of the orbit transfer vehicle and its equipments, a multi-parameter adjustable radiative shield is adopted in the passive thermal control method. The principle of the radiative shield by radiation heat transfer is first expounded and the multi-parameter adjustment strategy is then thoroughly analyzed. Taking a typical power system which is used in orbital transfer vehicle as an example, temperature evolutions of the storage tank, pipelines and electrical equipments are obtained by numerical simulations. The thermal control results of the radiative shield method, in which the multi-parameter adjustable characteristic is dominated, is compared with those of thermal insulation technique. Comparison results indicated that the proposed passive thermal control method completely takes advantage of the thermal inertia and radiative properties of the radiative shield, which extends the high thermal flux at both time and spatial domains.